2021
DOI: 10.3389/fped.2021.526779
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing in Neurodevelopmental Disorders

Abstract: Neurodevelopmental disorders are the most prevalent chronic medical conditions encountered in pediatric primary care. In addition to identifying appropriate descriptive diagnoses and guiding families to evidence-based treatments and supports, comprehensive care for individuals with neurodevelopmental disorders includes a search for an underlying etiologic diagnosis, primarily through a genetic evaluation. Identification of an underlying genetic etiology can inform prognosis, clarify recurrence risk, shape clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
114
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 317 publications
0
114
0
7
Order By: Relevance
“…One possibility is that sex chromosome gene effects contribute to ASD etiology. Indeed, mutations in many genes are known to increase the probability of ASD, and some of them, such as FMR1 , MeCP2 , and neuroligins 3 and 4, are on the X-chromosome ( Marco and Skuse, 2006 ; Guy et al, 2011 ; Percy, 2011 ; Zhang et al, 2017 ; Sledziowska et al, 2020 ; Savatt and Myers, 2021 ). While it will not be addressed here, excellent reviews that discuss the chromosomal contributions to sex differences in ASD can be found elsewhere ( Marco and Skuse, 2006 ; Guy et al, 2011 ; Percy, 2011 ; Zhang et al, 2017 ; Sledziowska et al, 2020 ; Savatt and Myers, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that sex chromosome gene effects contribute to ASD etiology. Indeed, mutations in many genes are known to increase the probability of ASD, and some of them, such as FMR1 , MeCP2 , and neuroligins 3 and 4, are on the X-chromosome ( Marco and Skuse, 2006 ; Guy et al, 2011 ; Percy, 2011 ; Zhang et al, 2017 ; Sledziowska et al, 2020 ; Savatt and Myers, 2021 ). While it will not be addressed here, excellent reviews that discuss the chromosomal contributions to sex differences in ASD can be found elsewhere ( Marco and Skuse, 2006 ; Guy et al, 2011 ; Percy, 2011 ; Zhang et al, 2017 ; Sledziowska et al, 2020 ; Savatt and Myers, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mutations in many genes are known to increase the probability of ASD, and some of them, such as FMR1 , MeCP2 , and neuroligins 3 and 4, are on the X-chromosome ( Marco and Skuse, 2006 ; Guy et al, 2011 ; Percy, 2011 ; Zhang et al, 2017 ; Sledziowska et al, 2020 ; Savatt and Myers, 2021 ). While it will not be addressed here, excellent reviews that discuss the chromosomal contributions to sex differences in ASD can be found elsewhere ( Marco and Skuse, 2006 ; Guy et al, 2011 ; Percy, 2011 ; Zhang et al, 2017 ; Sledziowska et al, 2020 ; Savatt and Myers, 2021 ). Another possible explanation for the sex differences observed in ASD is the differential regulation of sex hormones and their receptor-mediated signaling in females and males, leading to differential gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is a clear genetic link to ASD, genetic testing is recommended by both the American College of Medical Genetic and Genomics and the American Academy of Pediatrics following an ASD diagnosis ( Savatt and Myers, 2021 ). ASD is highly heritable, with estimates of twin heritability ranging from 70 to 90%, and recent advances in genetic research have identified over 100 gene or genetic variants associated with risk for ASD ( Johannessen et al, 2016 ; Genovese and Butler, 2020 ; Satterstrom et al, 2020 ; Savatt and Myers, 2021 ). As with many other conditions that have a genetic basis, ASD genetic testing can provide families with an expedited and clearer diagnosis, giving them access to appropriate educational or therapy services.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusive results from genetic tests can also provide comfort to families affected by ASD. They can ease anxiety and uncertainty, aid medical and legal planning, and even provide a sense of empowerment and reduced negative emotions for the parents ( Savatt and Myers, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation